A correlation between fractal growth, water contact angle, and SERS intensity of R6G on ion beam nanostructured ultra-thin gold (Au) films - Jasrotia, Priya; Priya, Bhanu; Kumar, Raj; Bishnoi, Priyanka; vij, Ankush; Kumar, Tanuj (Frontiers in Physics, 2023)
Introduction: This study focuses on the detection of rhodamine-6G using surface-enhanced Raman scattering (SERS) on gold nanostructures (AuNS) of different sizes. Ion beam irradiation has been carried out to tune the size of AuNS and investigate the underlying mechanisms of sputtering and diffusion that govern their growth. Additionally, the study established a correlation between fractal growth parameters, water contact angle, and SERS detection of R6G. The results of this study offer new insights into the mechanisms of SERS detection on roughened metallic surfaces. Methods: Thermal evaporation was used to deposit an Au thin film on a glass substrate. Subsequent 10 keV Ar+ irradiation was done on Au thin film for fluences ranging from 3×1014 to 3×1016 ions/cm2 to tune the size of AuNS. Rutherford backscattering spectroscopy (RBS) was used to confirm that the decrease in Au concentration under ion beam sputtering was responsible for the tuning in size and structure of AuNS. Fractal dimension (Df) and interface width (w) were used as statistical parameters to control the wettable characteristics of the AuNS surfaces. Results and discussion: The researchers found that the growth of AuNS was governed by ion beam induced sputtering and diffusion mechanisms. They established a correlation between fractal growth parameters, water contact angle, and SERS detection of R6G. They found that a higher surface coverage area of Au NPs with lower fractal dimensions and water contact angles favoured the SERS detection of R6G. This study provides new insights into the mechanisms of SERS detection on roughened metallic surfaces. It is found that the growth of AuNS was governed by ion beam-induced sputtering and diffusion mechanisms, and established a correlation between fractal growth parameters, water contact angle, and SERS detection of R6G. The findings of this study may have applications in the development of more sensitive and efficient SERS-based chemical sensors.